Pengaruh Literasi Digital Terhadap Psikologi Anak Sekolah Dasar - Khairin Revalia Ramadhani; Adrias Adrias; Aissy Putri Zulkarnaini (Institut Nalanda, 2025)
Digital literacy plays a crucial role in the psychological development of elementary school children, particularly in cognitive, social, and emotional aspects. In today's digital era, children grow up exposed to technology from an early age, making it essential to understand its impact. This study aims to analyze the influence of digital literacy on children's psychology by highlighting both the benefits and challenges it brings. The method used is a literature review, referring to various previous studies that discuss the relationship between digital literacy and children's psychological development. The results show that digital literacy provides numerous positive impacts, such as enhancing critical thinking skills, fostering creativity, and expanding children's communication and social interaction abilities. Access to digital information also enables children to better understand global social issues and develop empathy. However, excessive use of digital technology without proper supervision can lead to negative effects such as gadget addiction, social isolation, concentration problems, as well as exposure to inappropriate content and cyberbullying. Therefore, the role of parents, educators, and policymakers is vital in providing education, supervision, and appropriate guidance to children in using technology. This study emphasizes that digital literacy has a complex influence on children's psychology, requiring a balanced approach to maximize its benefits while minimizing its risks. With the right strategies, digital literacy can become an effective tool to support children's holistic development.